STRUCTURAL, ELECTRONIC AND VIBRATIONAL STUDY OF 4, 6-DICHLORO-5-METHYLPYRIMIDINE: A DFT APPROACH (Journal of Institute of Science and Technology, 2017)
Molecular structure, molecular electrostatic potential (MEP) and theoretical vibrational spectra of 4, 6-dichloro-5-methylpyrimidine (DMP) molecule have been presented in this paper. The vibrational spectra were calculated for monomer, dimer and unit cell DMP molecule using density function theory (DFT) and ab initio Hartree-Fock (HF) (for monomer) method employing 6-311++G (d, p) basis set using Gaussian 09 program. The frequencies obtained by DFT have smaller values than obtained from HF due to the inclusion of electron correlation in the previous one. Electronic absorption calculations are performed both in the gas and solvent phase using TD-DFT (including IEF-PCM model) to understand the stability, charge transfer and frontier molecular orbital energy gap. Large value of energy gap leads to the stability of molecule. Overlapping between calculated and the experimental structure show that the optimized geometry reproduced exactly similar structure as by the experiment.Journal of Institute of Science and TechnologyVolume 22, Issue 1, July 2017, Page: 51-60